An Update on Coronary Artery Disease and Chronic Kidney Disease - Baris Afsar; Kultigin Turkmen; Adrian Covic; Mehmet Kanbay (International Journal of Nephrology)
Despite the improvements in diagnostic tools and medical applications, cardiovascular diseases (CVD), especially coronary artery disease (CAD), remain the most common cause of morbidity and mortality in patients with chronic kidney disease (CKD). The main factors for the heightened risk in this population, beside advanced age and a high proportion of diabetes and hypertension, are malnutrition, chronic inflammation, accelerated atherosclerosis, endothelial dysfunction, coronary artery calcification, left ventricular structural and functional abnormalities, and bone mineral disorders. Chronic kidney disease is now recognized as an independent risk factor for CAD. In community-based studies, decreased glomerular filtration rate (GFR) and proteinuria were both found to be independently associated with CAD. This paper will discuss classical and recent epidemiologic, pathophysiologic, and clinical aspects of CAD in CKD patients.